(untitled) (Research, Society and Development, 2020)
In order to understand the burning patterns in the territory of Paragominas, Pará, in view of the strong relationship with the agricultural activities developed in the region and the negative implications that the use of fire provides to my environment, this work aims to spatialize and analyze the behavior of hot spots in the municipality, in the years 2000, 2015 and 2018. The areas affected by fires in the municipality were mapped for visual interpretation on standardized images. Qualitative and quantitative analyzes were used for the mapped data, with the aim of detailing the data regarding the panorama of the evolution of the fires. The geospatial data available for free by the Database of the Program for the Prevention and Control of Burnings and Forest Fires in the Legal Amazon (PROARCO) was handled. The Kernel method was used for the spatial distribution of the hot spots. The total number of outbreaks in the period between 2000, 2015 and 2018 was 34,323. Between the years 2015 and 2018, the municipality showed a decrease in the rate of occurrence of hot spots with 26,728 (77.87%) and 6,561 (19.11%), respectively. The year 2015 had the highest rate of fires, even after State intervention against deforestation. Therefore, it was observed that the incidence of hot spots in the municipality of Paragominas, is directly linked to agricultural activities practiced by farmers who live in the region, since the location is a reference in agricultural production in the Amazon.